Glycated hemoglobin as a marker of subclinical atherosclerosis and cardiac remodeling among non-diabetic adults from the general population - Haring, Robin; Baumeister, Sebastian E.; Lieb, Wolfgang; von Sarnowski, Bettina; Völzke, Henry; Felix, Stephan B.; Nauck, Matthias; Wallaschofski, Henri (Diabetes research and clinical practice, 2014)
Elevated glycated hemoglobin (HbA1c) is associated with increased risk of cardiovascular disease (CVD) and mortality but little is known about potential mechanisms underlying the reported associations. We used data from 1798 non-diabetic participants from the population-based cohort Study of Health in Pomerania (SHIP) to investigate cross-sectional and longitudinal associations of HbA1c with subclinical atherosclerosis (common carotid artery intima-media thickness [CCA-IMT]), cardiac structure (left ventricular mass [LVM]), and cardiac function (fractional shortening). Cross-sectional analyses revealed a positive association between HbA1c and mean CCA-IMT with a 0.02mm (95% confidence interval: 0.01–0.04) increase in CCA-IMT per 1% increase in HbA1c, and a similar positive trend across HbA1c quartiles (overall p-value <0.01). We also observed a graded association between HbA1c and high CCA-IMT (>75th percentile) with an odds ratio of 1.42 (95% CI: 1.11–1.81) per 1% increase in HbA1c. Longitudinal analyses showed no consistent associations of baseline HbA1c with mean follow-up CCA-IMT. There were no consistent associations of HbA1c with cardiac remodeling in cross-sectional and longitudinal analyses, respectively. The association between HbA1c and CCA-IMT in non-diabetic adults may be a crucial link between high-normal HbA1c levels and an increased risk of CVD and mortality.